2014
DOI: 10.1007/s13762-014-0512-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of an aerobic bacterial consortium able to degrade roxarsone

Abstract: Roxarsone is an organoarsenical compound used as food additive in the poultry industry. Roxarsone has the potential risk to contaminate the environment, mainly by the use of poultry industry manure as fertilizer, releasing inorganic arsenic to the soil and water. The aim of this work was to isolate and characterize a bacterial consortium capable to degrade roxarsone under aerobic conditions. A bacterial consortium was cultured from a soil sample obtained from a field fertilized with poultry litter containing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Therefore, it can be concluded that the key factor influencing the number of cells in the microcosms is the availability of nutrients and not roxarsone. Similar results were reported by Guzmán-Fierro et al (2014) in samples of agricultural soil fertilized with chicken manure feed roxarsone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it can be concluded that the key factor influencing the number of cells in the microcosms is the availability of nutrients and not roxarsone. Similar results were reported by Guzmán-Fierro et al (2014) in samples of agricultural soil fertilized with chicken manure feed roxarsone.…”
Section: Discussionsupporting
confidence: 89%
“…strain from chicken litter was able to degrade 100 % of roxarsone in 9 days (Stolz et al 2007) and that it can be biotransformed into inorganic arsenic . So far, there is only one report describing roxarsone biotransformation under aerobic conditions (Guzmán-Fierro et al 2014). Since, as reported by Shi et al (2014) and Stolz et al (2007), roxarsone can act as terminal electron acceptor in microbial respiration, microcosms cultured under anaerobic condition can be better biotransformers of roxarsone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data was analysed using two-way ANOVA and Student’s T test using the GraphPad Prism 5 software. P values <0.05 were considered as statistically significant [ 51 ]. Associations between variables were calculated by Pearson’s correlation.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a new metabolite of roxarsone, N-acetyl-4-hydroxy-m-arsanilic acid (N-AHAA), was identified (Yang et al 2016). These arsenical products can then contaminate soil, groundwater, and surface water (Morrison 1969; D r a f t 3 Mafla et al 2015;Guzmán-Fierro et al 2015), and the degradation process of roxarsone is greatly influenced by environmental factors such as temperature, humidity, and organic content (Sun 2012). However, the degradation rate and microbial community structure under different culture environment, such as aerobic, various lighting, and anaerobic conditions, have never been compared together.…”
mentioning
confidence: 99%